2006
DOI: 10.4025/actasciagron.v28i1.1284
|View full text |Cite
|
Sign up to set email alerts
|

Impacto do manejo nos atributos físicohídricos de um Latossolo Vermelho sob cerrado, no município de Selvíria, Estado do Mato Grosso do Sul

Abstract: RESUMO. Verificouse a influência da semeadura direta, convencional e quatro plantas de cobertura na condutividade hidráulica saturada, infiltração, retenção, armazenamento de água e potencial mátrico em um Latossolo Vermelho de cerrado cultivado com milho, na Unesp de Ilha Solteira, Estado de São Paulo. Utilizouse o delineamento experimental de blocos casualizados, no esquema em faixas com parcelas subdivididas, com 4 blocos. As parcelas foram constituídas pelas plantas de cobertura: Mucuna aterrima, Pennisetu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Su et al (2007) investigated the effects of conservation tillage practices on soil water storage, and verified that the highest water storage value after six years was obtained under NTS. Different results were obtained by Silva et al (2006), who observed greater water storage under the conventional than in the NTS. Nevertheless, the latter was more efficient in terms of available stored water for the plants.…”
Section: Soil Water Storage Variationmentioning
confidence: 65%
“…Su et al (2007) investigated the effects of conservation tillage practices on soil water storage, and verified that the highest water storage value after six years was obtained under NTS. Different results were obtained by Silva et al (2006), who observed greater water storage under the conventional than in the NTS. Nevertheless, the latter was more efficient in terms of available stored water for the plants.…”
Section: Soil Water Storage Variationmentioning
confidence: 65%
“…Soil structure also strongly affects the SWRC, mainly at high pressure heads (Klute, 1986;Stange & Horn, 2005). Changes in the soil porous system due to management practices or natural processes can lead to modifications in the amount and size of interaggregate pores, which greatly affect the shape and consequently, the slope of the SWRC (Silva, Alves, Sousa, & Fernandes, 2006;Cássaro, Borkowski, Pires, Rosa, & Saab, 2011). The soil organic matter content also influences the water retained at different potentials (Lal & Shukla, 2004).…”
Section: Introductionmentioning
confidence: 99%